Three new species of the genus Exphora Signoret, 1860 (Hemiptera, Fulgoromorpha, Tropiduchidae) from Madagascar - Junkiert, Łukasz; Walczak, Marcin (Zootaxa, 2015)
Three new species of the genus Exphora Signoret, 1860 (Hemiptera, Fulgoromorpha: Tropiduchidae) are described from Madagascar: E. constanti sp. n., E. stroinskii sp. n. and E. ambatolaonaensis sp. n. The male genitalia are described for the first time in this genus. The male genitalia, head and fore wing of the new species are illustrated with photos of habitus provided. Key to the known species of Exphora is given.